The Roman Potters' Kilns of Colchester - Hull, M.R (Reports of the Research Committee of the Society of Antiquaries of London, 1963)
This is an account of the excavation of eight kilns at Colchester, in Essex, England, found in the course of the work of the Colchester Excavation Committee in 1933 and in 1959. Included are descriptions of artefacts such as pottery and buildings, together with an account of the methodology used to unearth these.